Hepatoprotective effect of aqeous methanolic extract of Rumex dentatus in paracetamol induced hepatotoxicity in mice (Bangladesh Journal of Pharmacology, 2014)
Rumex dentatus is well known plant of Polygonaceae family which is widely used in traditional medicine to treat gastrointestinal tract. R. dentatus at doses 250 and 500 mg/kg significance decreased (p